Metabolomics of salivary fatigue markers in soccer players after consecutive games - Ra, S.-G.; Maeda, S.; Higashino, R.; Imai, T.; Miyakawa, S. (Applied Physiology, Nutrition, and Metabolism, 2014)
Strenuous and consecutive exercise leads to fatigue symptoms in athletes. Metabolomics is a comprehensive method to assess metabolites that involves the measurements of the overall metabolic signature of biological samples. Using metabolomic analysis, we investigated the identification of salivary fatigue markers in soccer players after 3 consecutive days of a game program. One hundred twenty-two male soccer players participated in 3 consecutive days of a game program. To detect fatigued athletes, we measured indices of traditional fatigue symptoms, i.e., heart rate, body mass and mood, before and after the program. We detected 37 fatigued players throughout the program. Before and after the program, the saliva in these players was analyzed using capillary electrophoresis and time-of-flight mass spectrometry (CE-TOFMS) and a multivariate statistical technique, principal component analysis, was used to process the data. CE-TOFMS was used to identify 144 metabolites in the saliva of fatigued players. A significant metabolomic difference was observed before and after 3 consecutive days of a soccer game program. Interestingly, metabolites were all increased after the program (P < 0.001). The identified metabolites, including 3-methylhistidine, glucose 1- and 6-phosphate, taurine, and some amino acids, were involved in skeletal muscle catabolism, glucose metabolism, lipid metabolism, amino acid metabolism, and energy metabolism. Our work demonstrated some salivary metabolites were significantly increased in the fatigued players after consecutive days of short soccer matches. We propose that the detected salivary metabolites may be new fatigue markers in athletes.